Europe unbound : enlarging and reshaping the boundaries of the European Union - Zielonka, Jan, 1955- (Routledge, 2003)
This book provides an analysis of the enlargement of the European Union. Drawing upon such diverse fields as history, sociology, political science and international relations.
Keywords: National security -- European Union countries.; European Union countries -- Politics and government.; European Union countries -- Emigration and immigration.; European Union countries -- Boundaries.; European Union countries -- Economic integration.; Europe -- Economic integration.; Pays de l'Union européenne -- Émigration et immigration.; Europe -- Intégration économique.; LAW -- International.; Boundaries; Emigration and immigration; International economic integration; National security; Politics and government; Europe; European Union countries; European Union.; European integration.; Migration.; Ethnic minorities.; Borders.; Community law.